2019
DOI: 10.17065/huniibf.482061
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Relationship Between the Level of Nomophobia and Subjective Well-Being of University Students: Ardahan Case

Abstract: Akıllı telefonlar çeşitli fonksiyonlarından ve kullanım kolaylıklarından dolayı kullanım oranı ve sıklığı sürekli artış gösteren önemli teknolojik cihazlardan biridir. Nomofobi diğer bir deyişle akıllı telefondan uzak kalma korkusu sürekli gelişen teknoloji ile birlikte son zamanlarda ortaya çıkan bir rahatsızlıktır. Mevcut çalışmada, Ardahan Üniversitesi"nde 2017-2018 öğretim yılı güz döneminde öğrenim gören öğrencilerin (N=395) nomofobi düzeylerinin öznel iyi olma (mutluluk) ile ilişkisi; Oxford Mutluluk Ölç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
2
0
2
Order By: Relevance
“…When this result of the study is examined in the light of literature, it can be said that women's spending more time with their smartphones and their checking their phones frequently both for the purposes of using the internet and also for other purposes is more effective in the development of nomophobia in women when compared with men. When the literature is reviewed in terms of the variable of age, it can be seen similar to the results of this study that there are studies which show that nomophobia does not differ significantly in terms of the variable of age (Güllüce, Kaygın and Börekçi, 2019;. On the other hand, there are also studies in literature which show that nomophobia differs significantly in terms of the variable of age .…”
Section: Results Discussion and Suggestionssupporting
confidence: 85%
See 3 more Smart Citations
“…When this result of the study is examined in the light of literature, it can be said that women's spending more time with their smartphones and their checking their phones frequently both for the purposes of using the internet and also for other purposes is more effective in the development of nomophobia in women when compared with men. When the literature is reviewed in terms of the variable of age, it can be seen similar to the results of this study that there are studies which show that nomophobia does not differ significantly in terms of the variable of age (Güllüce, Kaygın and Börekçi, 2019;. On the other hand, there are also studies in literature which show that nomophobia differs significantly in terms of the variable of age .…”
Section: Results Discussion and Suggestionssupporting
confidence: 85%
“…Alanyazında nomofobi ile ilgili çalışmalar günden güzen artmaktadır. Çalışmalara göre Nomofobi ile bağlantılı olan değişkenlerden bazıları, akıllı telefon kullanım sıklığı ve süresi (Bivin, Mathew, Thulasi ve Philip, 2013;Gezgin, Şumuer, Arslan ve Yıldırım, 2017;Gezgin, Şahin ve Yıldırım, 2017;Hoşgör, Tandoğan ve Gündüz-Hoşgör, 2017), yalnızlık ve utangaçlık (Bian ve Leung, 2014;Gezgin, Hamutoglu, Sezen-Gultekin ve Ayas, 2018;), sosyal stres ve öz-düzenleme yetersizliği (van Deursen, Bolle, Hegner ve Kommers, 2015), kişilik özellikleri (Öz ve Tortop, 2018), sosyal fobi (King ve diğ., 2013;Uysal, Özen ve Madenoğlu, 2016;Apak ve Yaman, 2019), öznel iyi oluş (Güllüce, Kaygın ve Börekçi, 2019), sosyal gelişmeleri kaçırma korkusu (Gezgin ve diğ., 2018;Yaman ve Kavuncu, 2019) ve sosyal medya bağımlılığı olarak sıralanabilir.…”
Section: Results Discussion and Suggestionsunclassified
See 2 more Smart Citations
“…The existing literature reports that staying away from the smartphone causes an increase in stress symptoms and temper in individuals (Polat, 2017); it also increases interpersonal sensitivity psychopathological symptoms such as obsessive-compulsive symptoms (Gonçalves et al, 2020). Besides, it is reported that nomophobia is related to social phobia (Apak & Yaman, 2019), loneliness (Karakuyu, 2019), depression (Büyükçolpan, 2019), happiness level (Güllüce et al, 2019), academic achievement (Erdem et al, 2016) and life satisfaction (Büyükalim, 2020). Nomophobia, which is becoming even more common with the increase in smartphone usage (Polat, 2017), shows itself as a symptom of disturbance due to limited smartphone usage (Ma & Liu, 2018).…”
mentioning
confidence: 99%